Determinants of Capital Structure: Panel Data Evidence from UK Firms - Li, Rui (2008)
This dissertation intends to analyse and examine the determinants of the capital structure with an unbalanced panel of 1504 listed UK companies from 2000 to 2007. A range of classical capital theories including Modigliani-Miller (M-M)irrelevance theory, the trade-off, pecking-order and agency theories, are deployed to explore and predict the signs and significance of each determinant pointed out by Titman and Wessels (1988) and Harris and Raviv (1991). In the investigation, we first employ the static panel-data models of the debt ratio, while profitability and firm uniqueness are negatively associated with leverage. In addition, we also find a positive relationship between earnings volatility and leverage, which, although counterintuitive, is consistent with the argument proposed by Myers (1977) and Donnelly (1993) that risky firms with less agency cost may be more aggressive on debt-financing than others. Further, two conflicting estimates of parameters are found (i.e. the estimated signs differ across regression specifications): the impacts of non-debt tax shields and growth opportunities. The sign of these relationships indicate that both the trade-off and pecking order theories offer sound explanations for the capital structure of UK listed companies. Finally, we find our regressions are more significant when the market value as opposed to book value of equity is adopted in the leverage ratio calculations.